Program for the use of energy-saving operational technological systems in the automation of technological processes (Texas Journal of Engineering and Technology, 2024)
Energy saving in the automation of technological processes is carried out with the help of energy-saving monitoring equipment through the software of the operating system. This system helps automate robotic processes to identify remote indicators to automatically implement energy-saving operations through technological system operations. Also, as another feature, the system only requires a local network to connect. Regardless of the technological system, the technical characteristics of the central monitoring equipment that ensures automatic operation and the automated energy-saving monitoring equipment are similar to each other. By objects designed to save energy, this system is the optimal operation of the heat source system, the adjustment of the temperature of the supply water. In the technological system, according to the system, it will be possible to change technological parameters such as heat source equipment, room temperature adjustment and outdoor air intake volume adjustment. Currently, the technical system operations manager has the role of performing these energy-saving operations, but finding the optimal value for each of these operations poses challenges. The operations manager is also responsible for tasks outside of facility operations, such as maintenance management, so regularly changing optimal settings can be a very problematic system. This system uses robotic process automation technology